Can hand involvement in osteoarthritis be as devastating as rheumatoid arthritis? (Annals of Medical Research, 2024)
Aim: Rheumatoid arthritis (RA) and osteoarthritis (OA) lead to pain and function loss in the hand joints. Common clinical symptoms include reduction in the range of motion in joints, muscle strength and hand functions. The present study aimed to compare hand involvement in RA and OA patients based on functionality, and to investigate the correlation between hand functions, radiological scores, and other disease parameters in RA and OA patients.Materials and Methods: The study was conducted with 56 RA patients and 51 hand OA patients. Hand functions were determined with hand grip strength, finger grip strength and Duruöz Hand Index in RA patients. Health Assessment Questionnaire (HAQ), Rheumatoid Arthritis Quality of Life Scale (RA-QoL) Short Form-36 (SF-36), Nottingham Health Profile (NHP), and Hospital Anxiety and Depression (HAD) scale were applied to all patients. Radiographic analysis of the hand joints was conducted with Modified Larsen and Modified Sharp scores in RA patients and the Kellegren-Lawrence score in OA patients.Results: Hand grip strength was lower in the RA group when compared to the OA patients (p0.05). There were significant correlations between Duruöz Hand Index, radiological scores, and other clinical parameters in both groups.Conclusion: Although RA could lead to serious deformation in hand joints, it was concluded that hand osteoarthritis could lead to disabilities induced by the loss of hand functions similar to RA and affect daily living activities.
Keywords: Rheumatoid arthritis; Osteoarthritis; Hand functions; Radiological scores